Data compression algorithms for sensor networks with periodic transmission schemes - Chen, Jianxin; Wang, Pengcheng; Ren, Xinzhuo; Meng, Haojie; Xu, Yinfei; Zhuge, Jiaqiang (MATEC web of conferences, 2022)
The operating state of switch cabinet is significant for the reliability of the whole power system, collecting and monitoring its data through the wireless sensor network is an effective method to avoid accidents. This paper proposes a data compression method based on periodic transmission model under the condition of limited energy consumption and memory space resources in the complex environment of switch cabinet sensor networks. Then, the proposed method is rigorously and intuitively shown by theoretical derivation and algorithm flow chart. Finally, numerical simulations are carried out and compared with the original data. The comparisons of compression ratio and error results indicate that the improved algorithm has a better effect on the periodic sensing data with interference and can make sure the change trend of data by making certain timing sequence.